2006
DOI: 10.1016/j.chemosphere.2005.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of microcystins by carbon nanotubes

Abstract: The production of cyanobacterial toxins microcystins (MCs) by cyanobacterial bloom which may promote the growth of tumor in human liver is a growing environmental problem worldwide. In this paper, the adsorption of MC-RR and LR, which were extracted from cyanobacterial cells in Dianchi Lake in China, by carbon nanotubes (CNTs), wood-based activated carbon (ACs) and clays were investigated. Compared with ACs and clay materials of sepiolite, kaolinite and talc tested, CNTs were found to have a strong ability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(63 citation statements)
references
References 23 publications
1
55
2
1
Order By: Relevance
“…It has been reported that CNTs functionalized with hydrophilic -OH and -COOH groups exhibited superior sorption for low molecular weight and polar compounds [18]. It has been also proposed that functionalized MWCNTs may provide an optimized approach for removal of target specific micropollutants [40]. However, our results revealed that the introduction of oxygencontaining functional groups decreased the adsorption capacity of MWCNTs for atrazine.…”
Section: Resultscontrasting
confidence: 55%
“…It has been reported that CNTs functionalized with hydrophilic -OH and -COOH groups exhibited superior sorption for low molecular weight and polar compounds [18]. It has been also proposed that functionalized MWCNTs may provide an optimized approach for removal of target specific micropollutants [40]. However, our results revealed that the introduction of oxygencontaining functional groups decreased the adsorption capacity of MWCNTs for atrazine.…”
Section: Resultscontrasting
confidence: 55%
“…The structure of CNTs resembles one (single-walled carbon nanotubes, SWCNTs) or more graphite sheets (multiwalled carbon nanotubes, MWCNTs) rolled up into a cylinder that consists of hexagon-rich sp 2 carbon at the wall and a few pentagons at the caps, getting more sp 3 -like as tube diameters become smaller (<0.7 nm) [11]. Because of the larger specific area and hydrophobic characteristic of the surface, CNTs have been regarded as a new kind of sorbent and have been studied for the removal of dioxin [12], trihalomethanes [13], microcystins [14], 1,2-dichlorobenzene [15], nicotine and tar [16]. They also showed satisfactory analytical potential as effective solid-phase extraction adsorbents for cyanazine [17], chlorotoluron [18], bisphenol A, 4-n-nonylphenol, 4-tert-octylphenol [19], chlorophenols [20], and several phthalate esters [21], non-steroidal anti-inflammatory drugs [22], and polybrominated diphenyl ethers [23].…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic biodegradation has been considered to be the main attenuation mechanism for MCs, and this process was reported to occur in diverse ecosystems, such as rivers [12], sand filters [11], reservoirs [20,21], coastal lagoons [22], lakes [17,23,24], and sewage effluent [25]. Bacterial strains of Sphingpoyxis sp.…”
Section: Introductionmentioning
confidence: 99%
“…The stable cyclic structure of MCs has presented many challenges to traditional water treatment technologies [16] where conventional processes, such as adsorption [17], ozone oxidation [18], photo-degradation [14], and electrochemical oxidation [19], have limited effect on their removal [11]. Aerobic biodegradation has been considered to be the main attenuation mechanism for MCs, and this process was reported to occur in diverse ecosystems, such as rivers [12], sand filters [11], reservoirs [20,21], coastal lagoons [22], lakes [17,23,24], and sewage effluent [25].…”
Section: Introductionmentioning
confidence: 99%